An experimental study of air entrainment and oxygen transfer at a water jet from a nozzle with air holes - Baylar, A; Emiroglu, ME (Wiley, 2004)
An adequate Supply of dissolved oxygen is important in natural rivers and in some water treatment processes. The dissolved oxygen concentration can be enhanced by entraining air bubbles in a receiving pool. When a water jet impinges a receiving pool at rest, air bubbles may be entrained and carried away below the pool free surface. This process is called plunging water jet entrainment and aeration. This paper describes an experimental study of the air entrainment rate and oxygen transfer efficiency of circular nozzles with and without air holes. In particular, the effect of varying the number, positions, and open/close status of the air holes is investigated. A negative pressure occurred depending on the air holes opened on the circular nozzles. This phenomenon affected the water jet expansion, water jet shape, air entrainment, and bubble penetration depth and, hence, the oxygen transfer efficiency. It was demonstrated that the air entrainment rate and the oxygen transfer efficiency of the circular nozzles, with air holes were better than those of the circular nozzles without air holes. Therefore, adding air holes to a simple, circular nozzle could lead to a significantly increased air entrainment rate and oxygen transfer efficiency.
Keywords: dissolved oxygen; oxygen transfer; air entrainment rate; aeration; water jet; nozzle